A Systematic Literature Review: Pembelajaran Matematika Berbasis E-Learning untuk Meningkatkan Literasi Matematis Siswa Indonesia - Arifatunnisak; Bambang Eko Susilo (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2023)
This study aims to describe the results of research on e-learning based mathematics learning to improve students' mathematical literacy in Indonesia. The method used in this study is a systematic literature review (SLR) by searching for articles using the Harzing's Publish or Perish application from Google Scholar and Scopus databases. The articles consists of 20 national and international articles indexed by SINTA and Scopus which were published in 2020-2023. The results of the study show that research related to e-learning-based mathematics learning to improve mathematical literacy has received quite good attention in recent years, indicated by research trends that continue to increase in the period 2020-2023. The majority of research was conducted at the junior high school level with the most used materials were trigonometry, statistics and quadrilaterals. The literature study was dominated by Java and Bali using quantitative research methods. Most of the research used the blended learning model and Google Classroom e-learning media, and e-learning based mathematics learning can be used effectively to increase students' mathematical literacy in Indonesia.